Effects of Production Costs and Operating Costs on Profit of PT Semen Baturaja (Persero) Tbk - Fasya Nadiah; RM Rum Hendarmin; Vhika Meiriasari (International Journal of Community Service & Engagement, 2022)
The objectives of this research are to determine the effect of production costs and operating costs on company profits at PT. Semen Baturaja (Persero) Tbk. The data investigated is an annual income statement for the period 2012 - 2019. The data is then analyzed using multiple linear regression. Further statistical tests revealed the variable production costs do not have a positive effect on company profits, but on the other hand, business costs have a positive effect on company profits. Furthermore, the coefficient of determination (R2) obtained a value of 0.890. This means that the variable production costs and business costs can explain the company's profit by 89% the rest is influenced by other variables not included in this study.